Using hedges in research articles of applied linguistics: Native and non-native patterns - Sahragard, Rahman; Ahmadi, Masoume; Zadeh, Naser Sabourian (Journal of Modern Languages, 2015)
Students and researchers need to be able to master hedging as one of the most significant resources for academics in order to be recognised as members of a scientific community and get their papers published in journals whose language of publication is English. This paper presents the results of reviewing 100 English language research articles (RAs) in applied linguistics, discussing the importance, frequency and distribution of hedging categories in different sections of RAs (namely Abstract, Introduction, Method, and Results) authored by native (NESs) and non-native speakers (NNESs) through employing Salager– Mayer’s (1994) classification. The analysis of Chi–square was conducted and the observed value of Chi-square (x2=5049.7≥ x2 obs= 3.84, df =1) showed that NESs and NNESs differed significantly in using hedges in their RAs. The findings indicated that in all sections but Introduction, non–native speakers outperformed their native counterparts in employing different hedging categories. NESs had hedged 48.7 times more than expected in the Introduction part while the frequency of hedges in other sections was lower than the expected rate; however, this rate was not the same for NNEs. Accordingly, the Introduction part may be considered as one of the major sections on which NNESs need to be given instructions to hedge as much as expected. NNESs must move beyond the view that the Introduction section of RAs is merely a detached and factual section which should be reported directly without reviewing the literature embedded therein.